2021
DOI: 10.1038/s41467-021-26956-8
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-assisted tumor localization of bacteria for enhanced biotherapy

Abstract: Despite bacterial-mediated biotherapies have been widely explored for treating different types of cancer, their implementation has been restricted by low treatment efficacy, due largely to the absence of tumor-specific accumulation following administration. Here, the conjugation of aptamers to bacterial surface is described by a simple and cytocompatible amidation procedure, which can significantly promote the localization of bacteria in tumor site after systemic administration. The surface density of aptamers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 62 publications
0
67
0
Order By: Relevance
“…6h , the most apparent tumor cell destruction, tissue necrosis and nuclear pyknosis are found in Trojan bacteria-treated group. As previously reported, the PPT-induced thermolysis of tumor cells would not affect the survival of neighboring non-tumor cells since the NIR light could precisely locate the tumor site, thereby minimizing the damage to surrounding normal tissue 19 , 30 , 32 , 33 , 38 , 39 , 48 . In addition, there was little difference between the trojan EC and VNP in terms of heating curve, fluorescence signal or survival time.…”
Section: Resultsmentioning
confidence: 72%
“…6h , the most apparent tumor cell destruction, tissue necrosis and nuclear pyknosis are found in Trojan bacteria-treated group. As previously reported, the PPT-induced thermolysis of tumor cells would not affect the survival of neighboring non-tumor cells since the NIR light could precisely locate the tumor site, thereby minimizing the damage to surrounding normal tissue 19 , 30 , 32 , 33 , 38 , 39 , 48 . In addition, there was little difference between the trojan EC and VNP in terms of heating curve, fluorescence signal or survival time.…”
Section: Resultsmentioning
confidence: 72%
“…Similarly, aptamers which promoted the colonization of bacteria inside tumor areas were also conjugated to S. typhimurium VNP20009 by Tan et al, which manifested excellent anti-tumor efficacy in 4T1 tumor-bearing mouse models. Moreover, the percentage of CD3 + CD4 + T cells and the production of IFN-g and TNF-a ware significantly elevated, suggesting strong immune response triggered by this bacterial agent (63). In another mouse model of triple negative breast cancer, impaired tumor growth and notable reduction in lung metastasis were reported in mice treated with E. coli encoding nanobody antagonist of CD47 (69).…”
Section: Breast Cancermentioning
confidence: 99%
“…In addition, an aptamer is an oligomeric nucleic acid that can specifically bind to a certain molecule and has similar ligand-receptor binding characteristics with the target molecule. By binding the aptamer AS1411 to the surface of S. typhimurium VNP20009, Geng et al observed nearly 2-fold and 4-fold enrichment after 12 and 60 hours in 4T1 and H22 tumorbearing mouse models compared to unmodified bacteria, showing the enhanced targeting performance of this bacterium(63).…”
mentioning
confidence: 99%
“…[5,22,23] We have recently exploited covalent conjugation, supramolecular interactions, and physical encapsulation to modify the bacterial surface and endow it with diverse extra functions. [24][25][26][27][28][29][30] Inspired by these achievements, we designed triple immune nanoactivators based on PDA nanoparticles conjugated with OVA antigen and α-PD-1 antibody and attached them to the bacterial surface by in situ interfacial polymerization using dopamine as a monomer.…”
Section: Design and Preparation Of Decorated Bacteriamentioning
confidence: 99%